Analisis Nilai-Nilai Sosial Budaya Dalam Seloko Adat Masyarakat Melayu Jambi - Putri Maharani Angelita (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
This research aims to analyze the socio-cultural values contained in Seloko Adat, a form of traditional oral literature that serves as a heritage of local wisdom for the Malay community in Jambi. Specifically, this study aims to identify, categorize, and evaluate the socio-cultural values in Seloko Adat and explore its role in the social life of the Jambi community. The research method employed is a literature study using secondary data from related articles, journals, and online news. The findings reveal that Seloko Adat is not only a literary work but also carries moral and ethical messages that influence the social life of the Jambi people. These values include togetherness, morality, cultural heritage, family rights and obligations, decency, equality, the importance of education, and environmental awareness. Seloko Adat also strengthens cultural identity, motivates behavior in accordance with societal expectations, and fosters closer family relationships. Thus, Seloko Adat has a positive impact on the social life of the Jambi community, enriching cultural values and preserving local identity.